A diffserv approach to enhance QoS in mobile IPv6 based networks - Ibrahim, Loay Faisal (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
Supporting Quality of Service (QoS) in the Internet is considered one of the main challenges facing many researchers nowadays. QoS is the ability of network elements (e.g. application, host and router) to provide some level of assurance for consistent network data delivery. The standard Mobile IPv6 was designed to allow nodes to be reachable and maintain ongoing connections while changing their location within the topology. However, it can only provide Best-Effort services to its applications, i.e. there is no QoS commitment offered. The Best-Effort service works fine with the conventional Internet applications (non real-time applications) such as remote login, electronic mail and file transfer. In contrary, real-time applications like video telephony and virtual conferencing require QoS guarantee in lieu of the Best-Effort delivery. As a result, Internet Engineering Task Force (IETF) has proposed three major models to support QoS in the Internet namely, IntServ, DiffServ and MPLS. Above all, the most promising one due to its simplicity and scalability advantages is DiffServ. Nevertheless, those approaches were initially designed without mobility inmind. Hence, they are not fully adapted to mobile environments yet. Integrating QoS with mobility support seems to be needed to fulfill the necessity of users. This dissertation aims to propose a new scheme that takes the advantage of DiffServ to enhance QoS in the mobile IPv6 networks. The proposed scheme was evaluated using two methods namely, simulation and analytical analysis. The proposed scheme is benchmarked with the standard MIPv6 which was proposed by IETF. The obtained results show that the proposed scheme outperforms the standard MIPv6 protocol in terms of packets loss and handover latency. Therefore, the probability of dropping BUs might reach to more than 20% in the MIPv6 which is adversely affects the handover performance. On the other hand when the BU is assigned with high priority as in the proposed scheme (DiffServ-MIPv6), the drop is not often encountered even if the network was congested.